Active control of base pressure in suddenly expanded flow for area ratio 4.84 - Ali Baig, Maughal Ahmed; Khan, Sher Afghan; Rathakrishnan, Ethirajan (International Journal of Engineering Science and Technology" (IJEST™), 2012)
Airflow from convergent-divergent axi-symmetric nozzles expanded suddenly into circular duct of larger cross-sectional area than that of nozzle exit area are studied experimentally, focusing attention on the base pressure and the flow development in the enlarged duct. Micro-jets of 1 mm orifice diameter located at 900 intervals along a pitch circle diameter (pcd) 1.3 times the nozzle exit diameter were employed as the controller of the base pressure. The tests are conducted for Mach numbers 1.87, 2.2 and 2.58. The area ratio of the present study is 4.84. The length-to-diameter ratio of the suddenly expanded duct is varied from 10 to 1 and nozzle pressure ratio (NPR) in the range 3 to 11. It is found that the active control in the form of blowing through small orifices (micro jets) are effective in controlling the base pressure field and even do not augment the flow field in the duct. An increase of 45 percent in base pressure was achieved for certain combination of parameters of the present study.